EFEKTIVITAS PUPUK KOMPOS DARI HASIL LUBANG RESAPAN BIOPORI TERHADAP TANAMAN SAWI ( Brassica juncea L. ) - Muhammad Alwi Akbar; Andi Sukainah; Kadirman Kadirman (Jurnal Pendidikan Teknologi Pertanian, 2018)
Compost is organic material, such as leaves, straw, reed, grass, rice bran, stalk corn, tendrils, herbs and manure that has been decomposed by decomposing microorganisms, so it can be utilized to improve soil properties. The purpose of this study is to determine the effectiveness of compost fertilizer from the results of biopori infiltration holes to mustard plants and to determine the compost concentration of biopori most influential on the growth of mustard plants. This type of research is experimental research conducted with two stages, namely composting in biopori infiltration hole and utilization of biopori compost fertilizer on mustard plant to increase the growth and production of mustard plant. This research uses descriptive analysis with 5 treatment of concentration of compost fertilizer. The results of this study indicate that fertilizer from biopori infiltration hole is effective for use and the most influential concentration on the growth of the mustard greens is 150 grams.